2020
DOI: 10.3390/en13082058
|View full text |Cite
|
Sign up to set email alerts
|

HTC of Wet Residues of the Brewing Process: Comprehensive Characterization of Produced Beer, Spent Grain and Valorized Residues

Abstract: Steady consumption of beer results in a steady output of residues, i.e., brewer's spent grain (BSG). Its valorization, using hydrothermal carbonization (HTC) seems sensible. However, a significant knowledge gap regarding the variability of this residue and its influence on the valorization process and its potential use in biorefineries exists. This study attempted to fill this gap by characterization of BSG in conjunction with the main product (beer), taking into accounts details of the brewing process. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 89 publications
(177 reference statements)
1
22
0
1
Order By: Relevance
“…The study deemed low temperatures of the HTC process especially suitable, thanks to the high content of hemicellulose in the feedstock [ 88 ]. Jackowski et al observed that the yield of HTC can be determined by an indirect method [ 89 ]. The study also confirmed that HTC could increase the heating value of BSG and decrease the O/C ratio [ 89 ], indicating its suitability as a valorization method suitable for subsequent pyrolysis.…”
Section: Thermal Valorization Of Bsgmentioning
confidence: 99%
See 2 more Smart Citations
“…The study deemed low temperatures of the HTC process especially suitable, thanks to the high content of hemicellulose in the feedstock [ 88 ]. Jackowski et al observed that the yield of HTC can be determined by an indirect method [ 89 ]. The study also confirmed that HTC could increase the heating value of BSG and decrease the O/C ratio [ 89 ], indicating its suitability as a valorization method suitable for subsequent pyrolysis.…”
Section: Thermal Valorization Of Bsgmentioning
confidence: 99%
“…Jackowski et al observed that the yield of HTC can be determined by an indirect method [ 89 ]. The study also confirmed that HTC could increase the heating value of BSG and decrease the O/C ratio [ 89 ], indicating its suitability as a valorization method suitable for subsequent pyrolysis.…”
Section: Thermal Valorization Of Bsgmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrochar OFG abundance tends to decrease with increasing reaction conditions such as reaction time, temperature, and water-to-biomass ratio [46][47][48]. For many feeds [50][51][52][53][54], HTC can be performed over the temperature range from 160-180 • C and at reaction times <12 h to promote formation of OFGs. More aggressive conditions (≥200 • C) are preferred for other applications [55].…”
Section: Introductionmentioning
confidence: 99%
“…Since the beer production process could significantly influence the properties of the corresponding BSG [82], the beer production process was performed in a controlled manner in a pilot-scale brewery and characterization of the main product of brewing (beer) is also an intrinsic part of this investigation. The residual BSG for further tests was produced in a pilot-scale brewing installation at the Wrocław University of Science and Technology.…”
Section: Methodsmentioning
confidence: 99%